Relative Price Stability, Creditor Rights, and Financial Deepening - Druck, Pablo; Dehesa, Mario; Plekhanov, Alexander (Washington, D.C. : International Monetary Fund, 2007)
The paper provides a theoretical and cross-country empirical analysis of the determinants of financial deepening, and finds that higher credit-to-GDP ratios are associated with stronger creditor rights and lower inflation, and that the marginal effect of improvements in creditor rights protection is declining as the rate of inflation increases. The analysis suggests that in a high inflation environment, controlling inflation and reducing macroeconomic volatility should be given priority. Once these goals are achieved, the focus of attention should shift to creditor rights protection and credit information management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet